1994
DOI: 10.1002/anie.199406551
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Third‐Order Nonlinear Optical Properties of a Conjugated Porphyrin Polymer

Abstract: Materials with large third-order optical nonlinearity are potentially useful for the fabrication of fast optical switches, but very few materials have sufficiently high susceptibility, ,yi3'. There is particular demand for materials with high ,y'3' ( > esu) in the near IR region (ca. 1 pm wavelength) for telecommunication switches. The molecular design features for a high xt3) material are poorly understood, although long conjugation lengths and low HOMO-LUMO gaps both appear to be important. ['] Porphyrins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
152
0
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(161 citation statements)
references
References 14 publications
5
152
0
4
Order By: Relevance
“…In the covalently linked porphyrin arrays, a variety of linkages such as ethyne [36,37], polyyne [38][39][40], ethylene [41], alkane [42,43] and aromatic entities [44][45][46] have been used to bridge the individual porphyrins. Lindsey et al have reported the synthesis of numerous phenylene-and diphenyl ethynyl-bridged multiporphyrins for mimicking the biological light-harvesting antenna systems and their photo physical properties have been studied [46][47][48].…”
Section: Multiporphyrins As Chemical Models For Photosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…In the covalently linked porphyrin arrays, a variety of linkages such as ethyne [36,37], polyyne [38][39][40], ethylene [41], alkane [42,43] and aromatic entities [44][45][46] have been used to bridge the individual porphyrins. Lindsey et al have reported the synthesis of numerous phenylene-and diphenyl ethynyl-bridged multiporphyrins for mimicking the biological light-harvesting antenna systems and their photo physical properties have been studied [46][47][48].…”
Section: Multiporphyrins As Chemical Models For Photosynthesismentioning
confidence: 99%
“…However, these porphyrin arrays show very weak ground-state electronic interactions between the porphyrin units. Various linear types of meso-to meso acetyleneand butadiyne-bridged multiporphyrins have also been reported and their photo physical and electrochemical properties have been determined [36][37][38]. In contrast to the arene-bridged porphyrin arrays, these types of multiporphyrins exhibit strong ground-and excitedstate interporphyrin electronic coupling.…”
Section: Multiporphyrins As Chemical Models For Photosynthesismentioning
confidence: 99%
“…Porphyrins have been incorporated into polymers as pendant groups, in the backbone of networks (36) and linear polymers and as coordination polymers. Thin films for catalysis studies have been prepared on electrodes by electropolymerization (37,38). Free-floating films, synthesized by interfacial condensation, can be supported on polymer membranes.…”
Section: Polyporphyrin Thin Filmsmentioning
confidence: 99%
“…[1][2][3][4] Наряду с этим, порфирины широко используются в медицине благодаря своей способности селективно накапливаться в злокачественных новообразованиях. Это уникальное свойство порфиринов лежит в основе фотодинамической терапии рака, а также для прове-дении флуоресцентной диагностики.…”
Section: Introductionunclassified